Mechanical detection of ultraslow, Debye‐like Li‐ion motions in LiAlO2 single crystals. Issue 7 (3rd August 2015) - Langer, Julia; Wohlmuth, Dominik; Kovalcik, Adriana; Epp, Viktor; Stelzer, Franz; Wilkening, Martin
Abstract : LiAlO2 serves as a suitable model system to study extremely slow Li ion transport properties in an oxide that is composed of corner‐shared LiO4 ‐polyhedra. The study represents one of the rare cases where both electrical and mechanical relaxation have been applied to monitor the same Li ion transport process in single crystals. Our results point to Debye‐like translational ion dynamics with an activation energy of ca. 1.12 eV. Abstract : Single crystalline LiAlO 2 is known as a very poor ion conductor. Thus, in its crystalline form it unequivocally disqualifies itself from being a powerful solid electrolyte in modern energy storage systems. On the other hand, its interesting crystal structure proves beneficial to sharpen our understanding of Li ion dynamics in solids which in return might influence application‐oriented research. LiAlO 2 allows us to apply and test techniques that are sensitive to extremely slow Li ion dynamics. This helps us clarifying their diffusion behaviour from a fundamental point of view. Here, we combined two techniques to follow Li ion translational hopping in LiAlO 2 that can be described by the same physical formalism: dynamic mechanical relaxation and electrical relaxation, i.e ., ionic conductivity measurements. Via both methods we were able to track the same transport mechanism in LiAlO 2 . Moreover, this enabled us to directly probe extremely slow Li exchange rates at temperatures slightly above 430 K. The results were compared with recent insights from nuclear magnetic resonance spectroscopy. Altogether, an Arrhenius‐type Li diffusion process with an activation energy of ca. 1.12 eV was revealed over a large dynamic range covering 10 orders of magnitude, i.e ., spanning a dynamic range from the nano‐second time scale down to the second time scale.